Comparison of Field and Laboratory Tests for Soil Suitability Assessment in Raw Earth Construction - Jacqueline Saliba; Walid Al-Shaar; Madeline Delage (Applied Sciences)
The demand for earth construction, primarily driven by environmental considerations, is currently growing. Earth, as a building material, has a very low carbon footprint and is easily recyclable, promoting a circular economy. It is also valued for its intrinsic qualities such as hygrothermal properties, air quality, acoustic performance, and esthetics. To meet this demand and promote earth construction, a better understanding of the local resources is essential. However, not all soils are suitable for earth construction, and their properties can significantly influence the final material performance. The assessment of soil suitability for earth construction requires both scientific rigor and practical field applicability. This study evaluates the correlation between traditional field-testing methods and standardized laboratory analyses through a comprehensive characterization of 39 soils from the Nouvelle-Aquitaine region in France. The research methodology integrated different field tests commonly used by practitioners, including sensory evaluations, plasticity tests, and cohesion assessments, with five standardized geotechnical tests covering particle size distribution, Atterberg limits, methylene blue value, organic matter content, and density measurements. The particle size distribution analysis revealed diverse soil compositions, with clay-sized particle content (<0.002 mm) ranging from 5% to 75%. Strong correlations were established between field and laboratory results, particularly between the cigar test and plasticity index (R2 = 0.8863), and between ring test scores and clay-sized particle content percentages, validating the reliability of traditional testing methods. Plasticity indices varied from 0% to 50%, indicating different soil behaviors and potential applications. These correlations demonstrate that while traditional field tests provide reliable preliminary assessment tools, laboratory testing remains essential for final material validation. The results demonstrate that while several soils are directly suitable for various earth construction techniques, other soils falling outside conventional recommendation envelopes may still be suitable for specific construction techniques when appropriately evaluated and may require modification through sieving, mixing, or stabilization.